2009
DOI: 10.1097/scs.0b013e3181acdf9a
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Outcomes Following Protocol Management in Crouzon, Pfeiffer, and Muenke Syndromes

Abstract: Patients with craniosynostosis syndromes are traditionally managed by a dedicated craniofacial unit. Optimal long-term management of these anomalies is unclear, but in the Australian Craniofacial Unit, it involves ongoing care by an integrated multidisciplinary team, following a protocol that commences at birth and continues until the patient reaches skeletal maturity. The Australian Craniofacial Unit has, for the last 35 years, collected a significant series of patients with these conditions who have complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
1
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 10 publications
2
18
1
10
Order By: Relevance
“…However, that study used a highly selected sample of patients referred to the hospital. 12 Noetzel and colleagues described intellectual functioning in children who have syndromic craniosynostosis and found FSIQs .90 in 71% of the 24 children in their sample, a percentage comparable to the finding of the current study with 63.2% of the children who have syndromic craniosynostosis obtaining FSIQs .90. 7 A syndromic craniosynostosis subgroup was not predictive of intellectual functioning in our study, with the sole exception of the small group of children who have Apert syndrome who obtained 19 Importantly, most of these previous studies, however, did not use standardized measures to assess behavioral and emotional problems or failed to report on the type of measures used.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, that study used a highly selected sample of patients referred to the hospital. 12 Noetzel and colleagues described intellectual functioning in children who have syndromic craniosynostosis and found FSIQs .90 in 71% of the 24 children in their sample, a percentage comparable to the finding of the current study with 63.2% of the children who have syndromic craniosynostosis obtaining FSIQs .90. 7 A syndromic craniosynostosis subgroup was not predictive of intellectual functioning in our study, with the sole exception of the small group of children who have Apert syndrome who obtained 19 Importantly, most of these previous studies, however, did not use standardized measures to assess behavioral and emotional problems or failed to report on the type of measures used.…”
Section: Discussionsupporting
confidence: 76%
“…[9][10][11] FSIQs of children who have Crouzon and Pfeiffer syndrome ranged from not testable to 115, but the majority of these children have FSIQs within the average range (90-110). 9,12 Mean FSIQs of patients who have Muenke and Saethre-Chotzen syndrome ranged from 50 to 120. [12][13][14][15][16] No published studies were found on intellectual functioning in children who have complex craniosynostosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical treatment may be required, for esthetic reasons and neurological complications 6 . In the treatment of these disorders, craniofacial surgery for cranial decompression performed in the first year of life is fundamental to avoid intracranial hypertension, which may have deleterious effects on the cognitive and linguistic development 7,8 . Regardless of the type or etiology, among craniofacial anomalies, this group represents a significant array of pathologies that may impair different functions of the central nervous system (CNS) during development of the children 9 .…”
mentioning
confidence: 99%